EXPLAINING THE UNITED STATES’ POLICY OF MILITARY WITHDRAWAL FROM AFGHANISTAN IN 2021: KEY DETERMINANTS - Sari, Annisa Uliana; Cahyaningtyas, June (Pena Wimaya, 2025)
ABSTRACT The United States’ military intervention and political involvement in Afghanistan persisted for over two decades following the events of 9/11. Under the narrative of the “global war on terror,” the U.S. implemented a range of military and diplomatic strategies to counter terrorism threats in Afghanistan. Throughout this period, various policies were enacted to support stabilization efforts and the eradication of terrorist groups. However, the U.S. decision to withdraw all military forces from Afghanistan in 2021 marked a critical turning point in its foreign policy, symbolizing the end of a long and controversial military intervention. This study aims to analyze the key factors driving the U.S. decision to withdraw its troops from Afghanistan. Employing a qualitative methodology and utilizing secondary data through library research, this research applies William D. Coplin’s decision-making theory to map the influence of various actors and variables within the policy process. The findings indicate that the withdrawal was primarily driven by considerations related to domestic political dynamics, economic and military capabilities, and the international context. These findings affirm that the troop withdrawal policy cannot be separated from the broader calculations of U.S. long-term national interests. Keywords: troop withdrawal, Afghanistan, United States, decision-making. ABSTRAK Intervensi militer dan keterlibatan politik Amerika Serikat di Afghanistan telah berlangsung selama lebih dari dua dekade sejak peristiwa 9/11. Dengan mengusung narasi “global war on terror”, Amerika Serikat menerapkan serangkaian strategi militer dan diplomatik untuk merespons ancaman terorisme di Afghanistan. Selama periode ini, berbagai kebijakan dilaksanakan untuk mendukung misi stabilisasi dan pemberantasan kelompok teror. Namun, keputusan Amerika Serikat untuk menarik seluruh pasukan militernya dari Afghanistan pada tahun 2021 menjadi titik balik dalam arah kebijakan luar negerinya yang menandai berakhirnya intervensi militer yang panjang dan kontroversial. Penelitian ini bertujuan untuk menganalisis faktor-faktor yang mendorong keputusan penarikan pasukan milter Amerika Serikat di Afghanistan. Penelitian dilakukan melalui metodologi kualitatif dan teknik pengumpulan data sekunder berbasis studi kepustakaan (library research). Teori pengambilan keputusan William D. Coplin digunakan untuk memetakan pengaruh berbagai aktor dan variabel dalam proses kebijakan. Hasil penelitian menunjukkan bahwa faktor-faktor yang mendorong kebijakan penarikan pasukan adalah pertimbangan dari situasi politik domestik, kapabilitas ekonomi dan militer, serta konteks internasional. Temuan ini menegaskan bahwa kebijakan penarikan pasukan tidak dapat dipisahkan dari kalkulasi kepentingan nasional jangka panjang Amerika Serikat. Kata kunci: penarikan pasukan, Afghanistan, Amerika Serikat, pengambilan keputusan.